Simulation of 2D Cavitation Bubble Growth Under Shear Flow by Lattice Boltzmann Model (Communications in Computational Physics, 2010)
Natural cavitation is defined as the phenomenon of the formation of vaporbubbles in a flow due to the pressure falls below the liquid's vapor pressure. The inceptionof the cavitation bubble is influenced by many factors, such as impurities, turbulence,liquid thermal properties etc. In this paper, we simulate a 2D cavitation "bubble" growth under shear flow in the inception stage by Single-Component-MultiphaseLattice Boltzmann Model (SCMP LBM). An empirical boundary condition sensitive 2Dbubble growth rate, R ∼ et , is postulated. Furthermore, the comparison is conductedfor bubble behavior under different shear rates. The results show that the cavitationbubble deformation is coincident with prior droplet theories and the bubble growthdecreases slightly with the flow shear rate.